Use of by-products for partial replacement of 3D printed concrete constituents; rheology, strength and shrinkage performance - Michail Papachristoforou; Vasilios Mitsopoulos; Maria Stefanidou (Fracture and Structural Integrity)
In this paper, fly ash, ladle furnace slag and limestone filler were utilized in concrete used as material for additive manufacturing (3D printing). Fly ash and ladle furnace slag were used as a replacement of cement (30% wt.) and limestone filler as a replacement of siliceous aggregates (50% wt.). Workability of fresh concretes that contained these by-products was measured 0, 15 and 30 minutes after mixing. Three different workability tests were conducted and compared: flow table, ICAR rheometer and an experimental method that measures the electric power consumption of the motor that rotates the screw extruder. Workability parameters that were measured were evaluated regarding printability of mixtures. Density, ultrasonic pulse velocity, compressive and flexural strength were measured on hardened concrete. Additionally, relative likelihood of cracking of different concrete mixtures was estimated by performing restrained shrinkage test (ASTM C1581). Results showed that use of fly ash or ladle furnace slag as binder, and limestone filler as aggregate decreases slightly the mechanical properties of concrete but improve its durability regarding cracking potential. Monitoring of electric power consumption of screw extruder motor was found to be an effective method for measuring easily real-time workability and define if a mixture is printable or not.